2005
DOI: 10.1210/en.2004-0761
|View full text |Cite
|
Sign up to set email alerts
|

Cyclic Adenosine 3′,5′-Monophosphate (cAMP) Enhances cAMP-Responsive Element Binding (CREB) Protein Phosphorylation and Phospho-CREB Interaction with the Mouse Steroidogenic Acute Regulatory Protein Gene Promoter

Abstract: Steroidogenic acute regulatory protein (StAR) transcription is regulated through cAMP-protein kinase A-dependent mechanisms that involve multiple transcription factors including the cAMP-responsive element binding protein (CREB) family members. Classically, binding of phosphorylated CREB to cis-acting cAMP-responsive elements (5'-TGACGTCA-3') within target gene promoters leads to recruitment of the coactivator CREB binding protein (CBP). Herein we examined the extent of CREB family member phosphorylation on pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
97
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(97 citation statements)
references
References 34 publications
0
97
0
Order By: Relevance
“…As illustrated in Fig. 9A, mLTC-1 cells treated with different factors for 30 min (Clem et al 2005, Manna et al 2006, increased P-CREB to varying levels. P-CREB appeared as a doublet and was enhanced approximately 2$2-, 3$1-, 1$9-, 2$7-, 1$8-, 2$9-and 4$8-fold over controls in response to IGF-I, EGF, FGF, TGFa, IL-1, CSF-1, and hCG respectively.…”
Section: Role Of Different Factors On Creb Phosphorylation and Its Rementioning
confidence: 83%
See 1 more Smart Citation
“…As illustrated in Fig. 9A, mLTC-1 cells treated with different factors for 30 min (Clem et al 2005, Manna et al 2006, increased P-CREB to varying levels. P-CREB appeared as a doublet and was enhanced approximately 2$2-, 3$1-, 1$9-, 2$7-, 1$8-, 2$9-and 4$8-fold over controls in response to IGF-I, EGF, FGF, TGFa, IL-1, CSF-1, and hCG respectively.…”
Section: Role Of Different Factors On Creb Phosphorylation and Its Rementioning
confidence: 83%
“…These studies demonstrated that the protein kinase C (PKC) signaling plays an important role in regulating StAR expression and steroidogenesis (Pilon et al 2003, as has the mitogen-activated protein kinase (MAPK) family of Ser-Thr kinases (Gyles et al 2001, Seger et al 2001, Manna et al 2002a, Martinelle et al 2004, Martinat et al 2005. In addition, StAR's transcriptional regulation has been shown to be mediated by several transcription factors, including the cAMP-response element-binding protein (CREB) and dosage-sensitive sex reversal, adrenal hypoplasia congenita, critical region on the X chromosome, gene 1 (DAX-1) (Manna et al 2002b, 2006, Clem et al 2005. In addition, the scavenger receptor class B type 1 (SR-B1), a high-density lipoprotein receptor, was shown to be involved in regulating steroidogenesis by facilitating the mobilization of precursor cholesterol into steroidogenic cells (Rao et al 2003, Manna et al 2006.…”
Section: Introductionmentioning
confidence: 99%
“…MA-10 cells were kindly provided by Dr. Mario Ascoli and maintained as described previously (33,34). These well studied mouse Leydig tumor cells produce progesterone as the major steroid in response to both LH and cAMP analogs.…”
Section: Methodsmentioning
confidence: 99%
“…Besides its effects on the immune system, ATF1 may also play a role in breast cancer via its regulation of steroidal hormone synthesis. Clem et al (Clem, Hudson, Clark 2005) showed that ATF1 binds the steroidal acute regulatory protein (StAR) promoter, although they failed to determine whether this association activates or blocks transcription. Regardless of ATF1's effect, regulation of StAR, an enzyme necessary for estradiol synthesis, may play an important role in preventing breast cancer because a longer time of exposure to estradiol (menarche to menopause) is correlated with increased breast cancer risk.…”
Section: Atf1mentioning
confidence: 99%
“…Houvras et al (Houvras and others 2000) found that wild type (wt) BRCA1 bound ATF1, causing transcription of a luciferase reporter gene. Such a finding strongly suggests (Ishiguro, 1997) StAR (Clem, 2005) Thrombospondin 1 (Ghoneim, 2007) Collagen, type X, α1 (Tsuchimochi, 2010) MMP13 (Tsuchimochi, 2010) Cyclin A (van Dam, 2001) Aromatase (Deb, 2006) MMP2 (Song, 2006) COX2 (Subbaramaiah, 2002) Cyclin D1 (Lee, 1999) Maspin (Maekawa, 2008) IFNγ (Xue, 2005) FoxP3 Fibronectin (Yin, 2010) Snail (Yin, 2010) Twist (Yin, 2010) Slug (Yin, 2010) av integrin (Yin, 2010) β6 integrin (Yin, 2010) E-cadherin (Yin, 2010) Increased malignancy Osteocalcin ( www.intechopen.com very few studies have been performed on the role of ATF1 in breast cancer. Important future studies will elucidate the effects of ATF1 on immunity and hormone synthesis in both normal and neoplastic breast cells, as well as its role in breast cancer in vivo.…”
Section: Atf1mentioning
confidence: 99%